2010
DOI: 10.1038/modpathol.2010.70
|View full text |Cite
|
Sign up to set email alerts
|

Primitive neuroectodermal tumors in patients with testicular germ cell tumors usually resemble pediatric-type central nervous system embryonal neoplasms and lack chromosome 22 rearrangements

Abstract: Primitive neuroectodermal tumors (PNETs) are one of the most frequent types of 'non-germ cell' tumor in patients with testicular germ cell tumors and have a guarded prognosis when present in metastatic sites after cisplatin-based chemotherapy. Improved treatments, including targeted therapy, require understanding the biology of these neoplasms. We therefore analyzed the morphologic, immunohistochemical and molecular biologic features of 14 PNETs from 14 patients with concurrent or previous testicular germ cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 28 publications
1
60
0
Order By: Relevance
“…In such scenarios, lesions at the metastatic sites can be misdiagnosed as an Ewing sarcoma or other small round blue cell tumor. Central-type PNET arising from germ cell tumors show a different immunostaining profile and lack the specific t(11: 22) translocation which is commonly present in Ewing sarcoma [3] . PNET arising from testicular germ cell tumors contain an isochromosome of the short arm of chromosome 12 [i(12p)], which is characteristic for all histological varieties of germ cell tumors of the testes [6] .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In such scenarios, lesions at the metastatic sites can be misdiagnosed as an Ewing sarcoma or other small round blue cell tumor. Central-type PNET arising from germ cell tumors show a different immunostaining profile and lack the specific t(11: 22) translocation which is commonly present in Ewing sarcoma [3] . PNET arising from testicular germ cell tumors contain an isochromosome of the short arm of chromosome 12 [i(12p)], which is characteristic for all histological varieties of germ cell tumors of the testes [6] .…”
Section: Introductionmentioning
confidence: 99%
“…PNET arising from testicular germ cell tumors contain an isochromosome of the short arm of chromosome 12 [i(12p)], which is characteristic for all histological varieties of germ cell tumors of the testes [6] . A study of 14 cases of central type PNET arising in the testes or metastatic sites revealed that CD57, a neuroendocrine marker, was most frequently positive, followed by synaptophysin, NeuN, and neurofilament [3] . Cytokeratin AE1/3 was positive in neural tubules in a minority of the cases classified as medulloepithelioma.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations